Adrenal Cushing’s syndrome in children - Guarnotta, Valentina; Emanuele, Fabrizio; Salzillo, Riccardo; Giordano, Carla (Frontiers in Endocrinology, 2023)
Adrenal Cushing's syndrome is a rare cause of endogenous hypercortisolism in neonatal and early childhood stages. The most common causes of adrenal CS are hyperfunctioning adrenal tumours, adenoma or carcinoma. Rarer causes are primary bilateral macronodular adrenal hyperplasia (PBAMH), primary pigmented adrenocortical disease (PPNAD) and McCune Albright syndrome. The diagnosis represents a challenge for clinicians. In cases of clinical suspicion, confirmatory tests of hypercortisolism should be performed, similarly to those performed in adults. Radiological imaging should be always combined with biochemical confirmatory tests, for the differential diagnosis of adrenal CS causes. Treatment strategies for adrenal CS include surgery and in specific cases medical drugs. An adequate treatment is associated to an improvement of growth, bone health, reproduction and body composition from childhood into and during adult life. After cure, lifelong glucocorticoid replacement therapy and endocrine follow-up are required, notably in patients with Carney's complex disease.